2021
DOI: 10.1097/mlr.0000000000001657
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Racial and Ethnic Disparities in Emergency Department Wait Time in the United States

Abstract: Background: Previous data over an extended period indicated that Black and Hispanic patients waited significantly longer than their White counterparts to see a qualified practitioner in US emergency departments (EDs).Objective: The objective of this study was to assess recent trends and sources of racial and ethnic disparities in patient wait time to see a qualified practitioner in US EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Additional public health research could explore the determinants of hesitancy over time, using culturally sensitive measures, as there could also be many alternative reasons why NH Black and NH white Detroiters may have differences in vaccine uptake, including issues of access. These could include difficulties in transportation, time costs for obtaining a vaccine, and lack of insurance [21][22][23]. Addressing these inequities will require investments in areas such as increasing vaccine subsidies and insurance coverage, more local vaccine sites, as well as testing culturally and linguistically sensitive vaccination messages.…”
Section: Discussionmentioning
confidence: 99%
“…Additional public health research could explore the determinants of hesitancy over time, using culturally sensitive measures, as there could also be many alternative reasons why NH Black and NH white Detroiters may have differences in vaccine uptake, including issues of access. These could include difficulties in transportation, time costs for obtaining a vaccine, and lack of insurance [21][22][23]. Addressing these inequities will require investments in areas such as increasing vaccine subsidies and insurance coverage, more local vaccine sites, as well as testing culturally and linguistically sensitive vaccination messages.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In addition, over the last decade, ED overcrowding and long wait times have been major health concerns. [7][8][9][10][11][12] Previously, it was reported that delayed ED visits for noncritically ill patients could result in a higher number of patients leaving before being seen by an ED provider leading to patient dissatisfaction. 13 Since the introduction of the Institute of Medicine report, several efforts have been made to raise awareness and develop broad-based policies to enhance health care quality, improve timeliness in EDs, and establish new guidelines to standardize the care process and reach equity.…”
mentioning
confidence: 99%
“…14,15 Moreover, initiatives at different levels of health care were implemented to reduce ED wait times and eliminate the existing disparities. 10,15,16 For instance, the American College of Emergency Physicians (ACEP) task force introduced a "high-impact" solution targeting ED overcrowding, and the passage of the Patient Protection and Affordable Care Act in 2010 has led to higher insurance coverage. 17,18 Since then, several studies have assessed the provision of emergency care for adult and pediatric populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations